2018
DOI: 10.1007/s13668-018-0239-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Behaviours Related to Dietary Salt Intake in High-Income Countries: a Systematic Review

Abstract: Overall (n = 24 studies across 12 countries), KAB related to dietary salt intake are low. While consumers are aware of the health implications of a high salt intake, fundamental knowledge regarding recommended dietary intake, primary food sources, and the relationship between salt and sodium is lacking. Salt added during cooking was more common than adding salt to food at the table. Many participants were confused by nutrition information panels, but food purchasing behaviours were positively influenced by fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 41 publications
9
41
1
1
Order By: Relevance
“…For example, the majority of participants were already aware that Australians eat too much salt, and that this is detrimental to health. This is a common finding within other population groups assessing salt-related knowledge [35], and suggests the need for better targeting of messages to less well informed segments of the population by future awareness campaigns. In comparison, at baseline, relatively few participants (less than a third) could correctly identify the recommended daily limit for salt of 5 g, a finding consistent within the literature [35], and this remained unchanged at follow-up.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, the majority of participants were already aware that Australians eat too much salt, and that this is detrimental to health. This is a common finding within other population groups assessing salt-related knowledge [35], and suggests the need for better targeting of messages to less well informed segments of the population by future awareness campaigns. In comparison, at baseline, relatively few participants (less than a third) could correctly identify the recommended daily limit for salt of 5 g, a finding consistent within the literature [35], and this remained unchanged at follow-up.…”
Section: Discussionmentioning
confidence: 68%
“…Education materials on this topic were disseminated throughout the campaign. Other studies frequently report that consumers find sodium information on food labels difficult to understand [35]. It is anticipated that educating consumers to accurately decipher labelled information can aid them in reading the label to make better food choices which contain less salt.…”
Section: Discussionmentioning
confidence: 99%
“…The most common intervention applied among adults or the general population is providing information to promote informed choices as a way of empowering consumers. Provision of information has different expressions: nutrition education [28,32,42], labelling [24,33,38,39,44], nutrition information in supermarkets and menus and packaged foods [38]. However, it also includes improved food literacy [42] as an empowering tool to help consumers make healthier food choices.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of 24 studies across 12 countries showed that while consumers were aware of the health implications of a high salt intake, fundamental knowledge regarding recommended dietary intake, primary food sources, and the relationship between salt and sodium was lacking. Moreover, many participants were confused by nutrition information panels, but food purchasing behaviors were positively influenced by front of package labelling [40].…”
Section: Introductionmentioning
confidence: 99%